Influence of hormonal induction and broodstock feeding on longfin yellowtail Seriola rivoliana maturation, spawning quality and egg biochemical composition. (4th September 2014) - Roo, J.; Fernández‐Palacios, H.; Schuchardt, D.; Hernández‐Cruz, C.M.; Izquierdo, M.S.
Abstract To optimize broodstock management for Seriola rivoliana, a survey over 5 years was performed to evaluate the effects of successive hormonal inductions with GnRHa or dietary regime on spawning quality. Running males and females with an oocyte diameter > 500 μm were injected with GnRHa. The spawning quality was compared among consecutive years and different moments along the spawning season. Besides, three different feeding regimes were tested. Spawning quality parameters were not significantly affected by time along the spawning season, whereas they were clearly influenced by diet. Particularly, broodfish fed the mackerel regime (M) showed a significantly higher number of eggs than other treatments. Besides, dietary protein content significantly improved broodstock fecundity of S. rivoliana. Moreover, hatching rates were also higher in broodfish fed mackerel and the dietary docosahexaenoic acid (DHA) levels significantly increased this parameter. Despite polar lipids were not significantly affected, neutral lipids fatty acid composition of S. rivoliana eggs showed higher 18:2n‐6 in eggs, whereas ARA content was not affected. The results of this study denoted the high fecundity and good spawning quality of S. rivoliana broodfish and suggested the importance of high protein, energy and DHA levels in broodstock diets.